Factors Affecting the Compressive Strength of Geopolymers: A Review - Droguett-Villalobos, T (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Geopolymers are created by mixing a source of aluminosilicates, which can be natural or by-products from other industries, with an alkaline solution. These materials based on by-products from other industries have proven to be a less polluting alternative for concrete production than ordinary Portland cement (OPC). Geopolymers offer many advantages over OPC, such as excellent mechanical strength, increased durability, thermal resistance, and excellent stability in acidic and alkaline environments. Within these properties, mechanical strength, more specifically compressive strength, is the most important property for analyzing geopolymers as a construction material. For this reason, this study compiled information on the different variables that affect the compressive strength of geopolymers, such as Si/Al ratio, curing temperature and time, type and concentration of alkaline activator, water content, and the effect of impurities. From the information collected, it can be mentioned that geopolymers with Si/Al ratios between 1.5 and 2.0 obtained the highest compressive strengths for the different cases. On the other hand, high moderate temperatures (between 80 and 90◦ C) induced higher compressive strengths in geopolymers, because the temperature favors the geopolymerization process. Moreover, longer curing times helped to obtain higher compressive strengths for all the cases analyzed. Furthermore, it was found that the most common practice is the use of sodium hydroxide combined with sodium silicate to obtain geopolymers with good mechanical strength, where the optimum SS/NaOH ratio depends on the source of aluminosilicates to be used. Generally speaking, it was observed that higher water contents lead to a decrease in compressive strength. The presence of calcium was found to be favorable in controlled proportions as it increases the compressive strength of geopolymers, on the other hand, impurities such as heavy metals have a negative effect on the compressive strength of geopolymers. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.